VALUER’S BEHAVIOURAL UNCERTAINTIES IN PROPERTY VALUATION DECISION MAKING - Mohammad, Nur Ezra; Mohd Ali, Hishamuddin; Jasimin, Tuti Haryati (PLANNING MALAYSIA, 2018)
Valuation is often said "an art and science". However, it is well known that valuation is more of an "art" than a “science” in which no two valuers could perhaps arrived at the same value. The disparities in the valuation variance pose a point of concern. This research attempts to identify the behavioural uncertainties during valuation decision making process. The finding reveals that there are six (6) elements of valuer's behavioural uncertainties, which include heuristic and bias, ethical conduct, client influence, valuer's experience and knowledge, availability and accuracy of market data, as well as negligence and professionalism.